Lessons Learned from the Battle in the Java Sea between the Imperial Japanese Navy and the American, British, Dutch & Australian Command Navies to Develop the Indonesian Maritime Defense - Aziz Ali Haerulloh; Lukman Yudho Prakoso; Rudi Sutanto (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2023)
This study aims to dissect the battle in the Java Sea between Japan and the Allies as a lesson learned in developing Indonesia's maritime defense. The research method is a descriptive qualitative approach to historical methods and thematic phenomenology. The results of this study show the weakening of maritime culture and changes in the cultural perspective of the people and the Dutch East Indies colonial government, which resulted in a massive and fast defeat process in sea battles that determined one of them, namely in the Java Sea. This event became a lesson for Indonesia to rebuild a maritime culture towards a world maritime axis country. Maritime Culture is the foundation for strengthening Indonesia's layered maritime defense system but with the availability of a fleet that has yet to reach the current Minimum Essential Forces (MEF) target.